2014
DOI: 10.3390/f5050862
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Forest Conservation for Water Quality Protection

Abstract: Abstract:Forests protect water quality by reducing soil erosion, sedimentation, and pollution; yet there is little information about the economic value of conserving forests for water quality protection in much of the United States. To assess this value, we conducted a meta-analysis of willingness-to-pay (WTP) for protecting unimpaired waters, and econometrically determined several significant drivers of WTP: type of conservation instrument (tool), aquatic resource type, geographic context, spatial scale, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 83 publications
(145 reference statements)
1
19
0
1
Order By: Relevance
“…Similarly, the multifunctional and holistic systems of IPs' water resource management, sometimes referred to as indigenous water cultures (McLean 2017), have been deemed effective at preventing pollution of freshwater environments (Hughey and Booth 2012; Shemsanga et al 2018). This includes traditional water purification methods (Opare 2017), complex systems of river zonation (Halim et al 2013), protection of sensitive areas (Dyck et al 2015), and forestry‐based systems of water quality protection (Kreye et al 2014; Camacho et al 2016). IPs' management practices also include remediation techniques (e.g., phytoremediation) to restore landscapes affected by pollution (Sistili et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the multifunctional and holistic systems of IPs' water resource management, sometimes referred to as indigenous water cultures (McLean 2017), have been deemed effective at preventing pollution of freshwater environments (Hughey and Booth 2012; Shemsanga et al 2018). This includes traditional water purification methods (Opare 2017), complex systems of river zonation (Halim et al 2013), protection of sensitive areas (Dyck et al 2015), and forestry‐based systems of water quality protection (Kreye et al 2014; Camacho et al 2016). IPs' management practices also include remediation techniques (e.g., phytoremediation) to restore landscapes affected by pollution (Sistili et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The positive relationship between these variables is generally supported by the literature. For example [16,50,[52][53][54][55] indicated that highly educated people and those with higher income are more supportive of nature preservation and have higher WTP.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…trade-off) or win-win (i.e. synergy) situation depending on the socioeconomic value placed by society to specific ecosystem services in a watershed (Kreye et al, 2014). For example if there is a demand for irrigation water, more timber will result in less water yield (win-loss); However, decreased timber from logging results in more water yield that can result in either more water for irrigation or increased runoff, sedimentation, and flooding (Dymond et al, 2012).…”
Section: Three-way Interactions Between Carbon Storage Timber Volumementioning
confidence: 99%